Egalitarianism, moral status and abortion: a reply to Miller - Räsänen, Joona (Journal of medical ethics, 2023)
Calum Miller recently argued that a commitment to a very modest form of egalitarianism—equality between non-disabled human adults—implies fetal personhood. Miller claims that the most plausible basis for human equality is in being human—an attribute which fetuses have—therefore, abortion is likely to be morally wrong. In this paper, I offer a plausible defence for the view that equality between non-disabled human adults does not imply fetal personhood. I also offer a challenge for Miller’s view.